A randomised study of outcome of acute pancreatitis in tertiary care hospital, Gujarat, India (retrospective study of 30 cases) - Jadav, Jayeshkumar S.; H. Shah, Parth (International Surgery Journal, 2018)
Background: Acute pancreatitis is common and lethal condition, often associated with one or more complications in varying degree. Aim of this study is to identify etiological factors and high-risk factors in the patients that can significantly alter the disease process and various presentations of acute pancreatitis and correlate them clinically to assess the severity of disease, to observe the clinical course of the disease, to predict beforehand the possible outcome clinically and to study the different prognostic factors evaluated on the basis of clinical assessment, serial laboratory and radiological investigations; to predict the clinical outcome of the disease, either favourable or unfavourable. Methods: In this retrospective study of randomly selected 30 patients admitted in G. G. Hospital Jamnagar, during the period of January 2015 to July 2016 with diagnosis of acute pancreatitis were studied. Their etiological, clinical, laboratory and radiological parameters were evaluated and their association with disease severity made. Impact of various parameters which can significantly alter the disease process was identified. Some of them required surgical intervention and rest of all were managed conservatively. Results: Most of patient (74%) recover well by conservative management. Only 26% patients required surgical management and mortality rate is 6.6% only. Conclusions: Study shows that not all patient of acute pancreatitis need surgical interventions, rather conservative approach is preferred over surgery now a day. Etiology of pancreatitis was most of the time idiopathic followed by cholelithiasis and alcoholism. Ascites and pleural effusion are two most common complications.